Controle por modelo preditivo aplicado a um conversor estático de potência trifásico com carga resistiva-indutiva - Nardi, Jeverton (2020)
This work aims to make a comparison between two different control methods for the current at the output of a three-arm, three-wire and three-phase converter with a star-connected resistive-inductive load. The first method uses a PID controller and the second method uses Model Predictive Control - MPC. In this work the modeling of the plant to be controlled and its discretization were carried out, later a study of the modulation space vector applied to the configuration of the converter and the plant with the obtaining of the limit plans and the separation plans, besides the switching sequence and the decomposition matrices. The discrete time model of the PID controller was obtained and later a study of the MPC aspects as a cost function, the predicted load current and the predicted reference current was carried out. The simulations were then documented through the presentation and explanation of the circuits, the codes used and the relevant graphics. It was concluded that the PID controller can work with reduced switching frequency, whereas the MPC controller presents a lower performance when working with reduced switching frequency, however it has the advantage of operating in non-linear systems, therefore the type of load and the characteristics of the microcontroller must be evaluated in order to define the control strategy to be used in each application. It was also observed that the output current of the converter obtained with the PID controller reached a noise level lower than the current obtained with the MPC.